2016
DOI: 10.18869/acadpub.aassjournal.4.4.43
|View full text |Cite
|
Sign up to set email alerts
|

Altered Motor Control in Athletes with Low Back Pain: a Literature Review

Abstract: Low back pain (LBP) is also one of the most common medical conditions in athletes. There is little doubt that patients with LBP use from their body differently than pain free individuals. The purpose of this review was to investigate changes in motor control which may be present in athletes with LBP. The search strategy for this review consisted of an electronic database search of full text in MEDLINE database. 28 studies met the eligibility criteria, most of which were cross-sectional in nature. The studies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Second, the laboratory conditions were different from the actual training conditions, which could have reduced the generalizability of the data. Third, since previous studies have shown that the mechanics of jump-landing differ in women from men (5,6), it seems that the findings cannot be generalized to male athletes; therefore, similar research is recommended to be carried out in men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the laboratory conditions were different from the actual training conditions, which could have reduced the generalizability of the data. Third, since previous studies have shown that the mechanics of jump-landing differ in women from men (5,6), it seems that the findings cannot be generalized to male athletes; therefore, similar research is recommended to be carried out in men.…”
Section: Discussionmentioning
confidence: 99%
“…Injuries to the lower limbs have been reported in jumplanding (5), and since these injuries reduce players' performance even after improvement (6), researchers are seeking the best techniques to minimize the risk of injury (7). Due to its need for frequent jumping, landing and sudden change of direction, volleyball is among the sports in which ACL injury has become increasingly common in the last decade, especially among women (8).…”
Section: Introductionmentioning
confidence: 99%
“…Further studies are required on other peoples with FHP or other postural changes, to clarify this problem more. Since movement mechanics differ between individuals with and without pain, the findings may not be generalizable to subjects who had FHP with neck pain or cervicogenic headache [38][39][40]. The study was limited to the eight weeks without follow up, so additional work with longer follow up better identifies the effect of training on the postural alignment.…”
Section: Modern Rehabilitationmentioning
confidence: 99%
“…This area has a particular importance in sports because it provides proximal stability for distal mobility [2]. Stability and the control of movement of the body core may improve one's performance and prevent further sports injuries [3]. The core muscles of body are divided into two main classes; the first class consists of the global muscles that are large and placed superficially and generate gross trunk movements.…”
Section: Introductionmentioning
confidence: 99%